Peningkatan Pemahaman Thaharah Melalui Media Audio Visual Pada Anak-Anak Di Desa Karangjaya - Ikhsan Kamil Surya; M. Ilyas Sikki; Setyo Supratno; Rika Sylviana (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2026)
This community service activity aimed to improve children’s understanding of thaharah through audio-visual media in Karangjaya Village, Pebayuran District, Bekasi Regency. Thaharah is a fundamental concept in Islamic education related to purification before worship. The activity consisted of educational videos, interactive lectures, ablution (wudhu) practice, and reflection sessions involving 15 children. Participants’ understanding was evaluated using pre-test and post-test assessments covering the meaning of thaharah, hadas and najis, purification tools, types of najis, and purification procedures. The pre-test results showed that only five participants correctly answered three questions, while the remaining ten answered only two. After the activity, the post-test indicated significant improvement, with twelve participants correctly answering all five questions, while three still required guidance. These findings were supported by the practical evaluation of wudhu, in which twelve children successfully performed the procedures correctly. The activity demonstrates that integrating audio-visual media with hands-on practice effectively enhances children’s understanding and practical skills related to thaharah and can serve as an engaging approach to Islamic religious education in the community.